Medicine Poisoning in Child - Vera Lígia Montenegro de Albuquerque; Luiza Jane Eyre de Souza Vieira; Denilce Alves Alcântara (Revista Brasileira em Promoção da Saúde, 2003)
The aims of this study were to identify the main medications responsible for exogenous poisoning of children attended at a referral emergency hospital of Fortaleza, Ceará State,Brazil; to describe the most prevalent age and gender, as well as the main reactions presented by poisoned children. It was a documental retrospective study of 203 records of patients attended in 1997 at the Toxicology Center of Ceará. Our results showed that antidepressants, bronchodilators and vitamins were the most common agents; 77% of poisoned children were between 1 and 4 years of age, and 54% were males; somnolence, psicomotor excitement, tachycardia and vomiting were the most commonly encountered reactions. In conclusion, these medicines represents an important cause of children poisoning, Families must attempt to the safe storing and dealing with these products. It is mandatory that the government determines the utilization of special packages for children protection in our country.